HIV risk perception and sexual behavior among HIV-uninfected men and transgender women who have sex with men in sub-Saharan Africa: Findings from the HPTN 075 qualitative sub-study - Yamikani R. Mbilizi Chimwaza; Sufia S. Dadabhai; Alinane L. Nyondo Mipando; Calvin Mbeda; Ravindre Panchia; Jonathan P. Lucas; Wairimu Chege; Erica L. Hamilton; Theodorus G. M. Sandfort (PLOS Global Public Health, 2022)
There remains a limited understanding of how men who have sex with men (MSM) and transgender women (TGW) in sub-Saharan Africa (SSA) perceive their risk for HIV and how risk influences behavior during sexual interactions. We performed thematic analysis on in-depth interviews from the qualitative sub-study of HPTN 075 in Kenya, Malawi, and South Africa. Using the Integrated Behavioral Model (IBM) constructs, we found that most MSM and TGW perceived themselves to be at risk for HIV, leading them to regularly engage in safer sexual behaviors. Notably, even though these MSM and TGW perceived themselves to be at risk for HIV, some of them reported engaging in transactional sex, sex under the influence of alcohol, and intentional non-use of condoms. This indicates that HIV risk perception was not always associated with safer sexual behaviors or a reduction in risk behaviors. Attitudes (negative attitudes toward condom use), perceived norms (social pressures), and environment constraints (contextual barriers) were related to MSM and TGW not engaging in safe sexual behavior. Hearing the perspectives of MSM and TGW on their sexual behavior continues to be important for the development and implementation of effective prevention policies and interventions. Eliminating structural barriers such as stigma, discrimination, and criminalization of same-sex sexuality is a crucial prerequisite for the success of interventions to promote sexual health among MSM and TGW in SSA.